Not all models are created equal: assessing parameterisations of iron dynamics in ocean biogeochemical models - Rogerson, Jonathan J (Department of Oceanography, 2020)
Iron is one of the most commonly studied trace metals as it exerts a significant influence on ocean productivity, carbon sequestration as well as modulating atmospheric CO2 concentrations. As iron is such a vital nutrient for biogeochemical processes it is often included as a variable in ocean biogeochemical models. In representing the iron cycle, biogeochemical models must parameterise the major processes of uptake by phytoplankton, remineralisation and scavenging. However, there is no generally accepted set of equations to represent iron dynamics and thus a variety of different parameterisations are employed across the modelling community. The thesis work focussed on the inorganic iron parameterisations with an emphasis on the scavenging formalisms which are employed in current biogeochemical models. Using an open-source numerical model (Biogeochemical Flux Model, BFM) as a background model, a more advanced inorganic iron parameterisations that simulates free iron scavenging and ligands linked to dissolved organic carbon (DOC) (from the open-source model PISCES) was included and compared to assess the implications on iron cycling and plankton community structure. The parameterisations were compared by running box models (0D) in four different regions: Southern Ocean, Equatorial Pacific, North Atlantic gyre and North-east Pacific, representing different types of iron dynamics. The free scavenging model (FePISCES) resulted in dissolved iron concentrations being two to three times greater than with the standard formulation (FeBFM), which used a simpler formalism for scavenging. Consequently, the elevated iron concentrations in FePISCES resulted in altered community compositions for phytoplankton which impacted the seasonal cycle of macronutrients and chlorophyll concentrations. Furthermore, the prognostic appreciation of ligand dynamics in FePISCES lead to a decoupling of dissolved iron from its organic species with the DOC content for a region being indirectly implicated in driving the iron system by affecting the scavenging regime. Therefore, using a different set of iron parameterisations will alter the biogeochemical behaviour of a model. The results suggest that the testing of parameterisations should be initially done within 0D models in order to assess any non-linear behaviours and ultimately embedded in 3D models to study how they interact with physics.